2016
DOI: 10.1111/asj.12647
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between length of productive life and lifetime production efficiency in a commercial swine herd in Northern Thailand

Abstract: Genetic parameters and trends for length of productive life (LPL), lifetime number of piglets born alive per year (LBAY), lifetime number of piglets weaned per year (LPWY), lifetime litter birth weight per year (LBWY) and lifetime litter weaning weight per year (LWWY) were estimated using phenotypic records of 3085 sows collected from 1989 to 2013 in a commercial swine farm in Northern Thailand. The five-trait animal model included the fixed effects of first farrowing year-season, breed group and age at first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
2
1
Order By: Relevance
“…Differently, positive favourable genetic and phenotypic correlations were found between longevity (LPL) and lifetime production traits (LNL, LTP and LTP365). These results agree with previous studies (Sobczyńska et al, 2013;Noppibool et al, 2017). It also demonstrates that sows with higher EBV and phenotypic values for lifetime production traits are kept longer in the herd.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 1 more Smart Citation
“…Differently, positive favourable genetic and phenotypic correlations were found between longevity (LPL) and lifetime production traits (LNL, LTP and LTP365). These results agree with previous studies (Sobczyńska et al, 2013;Noppibool et al, 2017). It also demonstrates that sows with higher EBV and phenotypic values for lifetime production traits are kept longer in the herd.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Contrarily to litter size traits, few studies are available for reproduction traits related to production intervals or longevity. Even though, in our study, the estimated heritability for FIT was lower than the mean value achieved by Akanno et al (2013) The length of productive life (LPL) is commonly defined as time (days) between the sow age at first farrowing and the age at culling/mortality (Yazdi et al, 2000;Serenius and Stalder, 2007), last farrowing (Sobczyńska et al, 2013) or weaning of last litter (Noppibool et al, 2016;Noppibool et al, 2017). In our study, many sows had only one registered litter as they were kept off breeding prematurely, ergo LPL was defined as time from birth to last farrowing.…”
Section: Accepted Manuscriptcontrasting
confidence: 68%
“…The h 2 estimates for PSY traits were also low. Noppibool et al (2017) reported h 2 of 0.07 ± 0.03 for NBA PSY and 0.13 ± 0.03 for NW PSY in purebred sows (Landrace and Yorkshire). Abell et al (2013) reported an h 2 of 0.11 ± 0.01 in a study including Landrace, Large White, and F1 sows.…”
Section: Heritabilitiesmentioning
confidence: 97%
“…The h 2 estimates for PSY traits were also low. Noppibool et al (2017) reported h 2 of 0.07 ± 0.03 for NBA PSY and 0.13 ± 0.03 for NW PSY in purebred sows (Landrace and Yorkshire). Abell et al (2013) reported a h 2 of 0.11 ± 0.01 in a study including Landrace, Large White, and F1 sows.…”
Section: Heritabilitiesmentioning
confidence: 97%